Kontekstualisasi Teologi Keadilan Dalam Hukum Qisas Dan Poligami - Bakry, Kasman; Gunawan, Edi (Prodi Hukum Pidana Islam Fakultas Syari?ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Abstract: Principles of justice in both of al-Qur'an and al-hadith mean: equality (al-musâwâh), honesty (al-shidq), and purity (al-ikhlâsh). Islam is a religion that upholds the value of justice. Even, justice is the main character of the Prophet Muhammad (Peace be Upon Him)  and Muslims. However, Islamic criminal law, which contains of those three values, has many problem to be criticized particularly on some applications such as the punishment of qishāsh, the practice of polygamy. They are considered not to reflect the value of justice. The main problem of this research is the contextualization of theological justice in the law of qishash and polygamy, using a normative theological approach. The conclusions are that the values of justice which found in the application of the punishment of qishāsh and the practice of polygamy contain wisdom and benefit for mankind. Keywords: Theology, justice, qishash, polygamy.   Abstrak: Prinsip keadilan dalam al-Qur’an dan hadis meliputi makna antara lain: kesetaraan (al-musâwâh), kejujuran (al-shidq), dan kemurnian (al-ikhlâsh). Islam adalah ajaran yang menjunjung tinggi nilai keadilan, bahkan sisi keadilan merupakan karakter Rasulullah saw dan umat Islam. Namun nilai keadilan tersebut dikritisi pada beberapa penerapan hukum pidana Islam, seperti hukuman qishâsh, dan pada praktik poligami dalam perkawinan, yang dianggap tidak mencerminkan nilai keadilan. Pokok permasalahan penelitian ini adalah kontekstualisasi teologi keadilan dalam hukum  qishâsh  dan poligami, dengan menggunakan pendekatan teologi normatif. Kesimpulannya bahwa nilai-nilai keadilan terdapat pada penerapan hukuman qishâsh dan praktik poligami dalam perkawinan, dan mengandung hikmah bagi kemaslahatan umat manusia. Kata Kunci: Teologi, keadilan, qishâsh, poligami.